(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
CENTENARY OF JORDAN PARK 1989 was the centenary of the oldest in Poland (and one of the oldest in the world) parks for children and youth, Jordan Park in Cracow, established by Dr. Henryk Jordan (1842-1907), a Cracow doctor, professor at the Jagiellonian University, community leader and outstanding teacher. In this park, education went hand in hand with outdoor recreation and play. Forty five busts of great Poles placed there had an important place in a program of patriotic education. Choral singing in the park, lectures on the history of Poland, symbols on uniforms, distinctions, and cultivation of national traditions, all helped to keep up the Polish spirit in the young generation during the Partitions. After the death of its founder in 1907, the park slowly changed in appearance, and the activities there changed as well. Finally, with the outbreak of the First World War, the park ceased to function for some time. During that time some playing fields, green areas, trees, busts and postuments were destroyed. The Second World War was even worse yeat for the park. Most of the trees were replanted near a Hitler-Jugend stadium then under cosntruction; the occupiers intended to destroy the statues exposed by this operstion, and it was only thanks to one of Dr. Jordan’s pupils that they were saved. After the Second World War, work on restoring the park’s previous appearance gradually went forward. The central circle with its statues was reconctructed after its former design; te rescued busts were placed, and several missing statues were reconstructed. Presently, Jordan Park, rich in historic values, a worldscale monument and a monument of Polish culture is, unfortunately, losing its former functions. Though the Dr. Henryk Jordan Park Society, established in 1957, has made efforts toward the restoration of Jordan’s traditions, youth activities were not restarted, and only occationaly have cultural and recreational events taken place in the park.